2017
DOI: 10.1089/vbz.2017.2111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Survey and Genetic Characterization ofAnaplasmaSpecies in Mongolian Livestock

Abstract: Anaplasma species are obligate intracellular rickettsial pathogens that cause great economic loss to the animal industry. Few studies on Anaplasma infections in Mongolian livestock have been conducted. This study examined the prevalence of Anaplasma marginale, Anaplasma ovis, Anaplasma phagocytophilum, and Anaplasma bovis by polymerase chain reaction assay in 928 blood samples collected from native cattle and dairy cattle (Bos taurus), yaks (Bos grunniens), sheep (Ovis aries), and goats (Capra aegagrus hircus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…A. phagocytophilum is now the most prevalent species of Anaplasma over broad areas where various tick species are vectors (Cao et al, 2000 ; Villar et al, 2015 ; Eisen, 2018 ). This species infects the neutrophils of cattle, sheep, goats, horses, dogs, hares, yaks, and 24 species of rodents (Kawahara et al, 2006 ; de la Fuente et al, 2016 ; Ochirkhuu et al, 2017 ; Rocchigiani et al, 2018 ). A. phagocytophilum has also been associated with HGA in China since 2008 (Wormser, 2016 ), and cases of HGA have been reported in Europe and North America (Thomas et al, 2009 ; Nichols Heitman et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A. phagocytophilum is now the most prevalent species of Anaplasma over broad areas where various tick species are vectors (Cao et al, 2000 ; Villar et al, 2015 ; Eisen, 2018 ). This species infects the neutrophils of cattle, sheep, goats, horses, dogs, hares, yaks, and 24 species of rodents (Kawahara et al, 2006 ; de la Fuente et al, 2016 ; Ochirkhuu et al, 2017 ; Rocchigiani et al, 2018 ). A. phagocytophilum has also been associated with HGA in China since 2008 (Wormser, 2016 ), and cases of HGA have been reported in Europe and North America (Thomas et al, 2009 ; Nichols Heitman et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have documented spotted fever group (SFG) Rickettsia ,(Lewin et al, 2003; Papageorgiou et al, 2012; Speck et al, 2012) Borrelia burgdorferi, (Masuzawa et al, 2014; Papageorgiou et al, 2012; Scholz et al, 2013; Walder et al, 2006) Anaplasma spp .,(Haigh et al, 2008; Javkhlan et al, 2014; Masuzawa et al, 2014; Papageorgiou et al, 2012; Walder et al, 2006; Ybanez et al, 2013) and tick-borne encephalitis virus (TBEV)(Frey et al, 2012; Muto et al, 2015) in Mongolia, but most were limited by their sample sizes and small geographic coverage. A recent molecular study of Anaplasma species detected in Mongolian cattle, yaks, goats, and sheep found 33.2% – 44.5% of livestock screened, tested positive, suggesting a high burden of disease in the capital city of Ulaanbaatar (Ochirkhuu et al, 2017). However, this study targeted A. marginale and A. ovis which do not infect humans.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, only A. phagocytophilum could be detected by PCR and the role of these ticks as vectors for other Anaplasma spp. present in Mongolian livestock (Ochirkhuu et al 2017) could not be determined here.…”
Section: Distribution Of Ticks and Their Possible Roles As Vectorsmentioning
confidence: 81%
“…and Borrelia spp. were detected in Mongolian ticks (Fomenko et al 2009;Scholz et al 2013;Masuzawa et al 2014;Iwabu-Itoh et al 2017;Javkhlan et al 2014), livestock (Papageorgiou et al 2012;Karnath et al 2016;Ochirkhuu et al 2017) and humans (Walder et al 2006;von Fricken et al 2018). Piroplasms were detected in ticks (Battsetseg et al 2001(Battsetseg et al , 2002Boldbaatar et al 2005;Tuvshintulga et al 2015Tuvshintulga et al , 2016Karnath et al 2016), livestock (Avarzed et al 1997;Ruegg et al 2007;Altangerel et al 2011Altangerel et al , 2012Sivakumar et al 2012;Munkhjargal et al 2013;Yoshinari et al 2013) and humans (Hong et al 2014) in Mongolia.…”
Section: Introductionmentioning
confidence: 99%